Kinerja Keuangan Kelompok Bank berdasarkan Modal Inti 1 Sebelum dan Sesudah diberlakukannya POJK Fintech - Amalia Putri Kusuma; Siti Hidayati (Research Center and Case Clearing House PPM School of Management, 2023)
This study aims to determine differences in the financial performance of Bank Groups Based on Core Capital I (KBMI I) registered with the Financial Services Authority before and after the enactment of POJK Fintech number;13/POJK.02/2018 Regarding Digital Financial Innovation in the Financial Services Sector. The observation period is three years before the implementation of the POJK Fintech (2015–2017) and three years after the implementation of the POJK Fintech (2018–2020). The research data was obtained from the financial reports of Bank KBMI 1, which the Financial Services Authority published during 2015–2020. The research technique used was probability sampling, and obtained 51 banks as samples in this study from the number of Bank KBMI 1 as many as 58 banks. The data processing process uses SPSS 26 assistance and analysis techniques of Paired Sample T-Test and Wilcoxon Sign Rank Test. After processing the data, the results showed differences in profitability before and after the implementation of POJK Fintech Bank KBMI 1. There were no differences in liquidity and capital of Bank KBMI 1 before and after the implementation of POJK Fintech. Based on the results of this study, Bank KBMI 1 may consider adding to the innovation of Bank services and products related to financial management in assessing the Bank's financial performance, especially to increase the level of profitability of the Bank.